Within and beyond the imperial boundaries : rethinking Ottoman literary modernization process together with Halit Ziya Uşaklıgil and Krikor Zohrab - Bakırcı, Fatma Betül (My University, 2020)
On dokuzuncu asrın sonuna doğru Osmanlı İmparatorluğu'nda edebi modernleşme gelişim göstermeye başlar. Çoğul ve çok kültürlü bir yapıya sahip olan imparatorluk sahasında ivme kazanan bu hareketin de etkisiyle kültürler arasında kuvvetli diyaloglar gerçekleşir, milletler etkileşime açık öznelere dönüşürler. Bu tezin en önemli amacı Krikor Zohrab ve Halit Ziya Uşaklıgil ile birlikte on dokuzuncu asrın ortasından itibaren modernleşen Türkçe ve Ermenice edebiyatı yan yana okumak ve böylelikle buradan bir paralel modernleşme anlatısı üretmektir. İkinci olarak, bu yazarlar karşılaştırarak dönemin kültürel ortamına, Türkçe ve Ermenice edebiyat arasındaki sürdürülen diyaloglara, uzlaşı ve çatışmalara yakın temas edilmesi amaçlanır. Böylelikle bu çalışmada Krikor Zohrab ve Halit Ziya Uşaklıgil etrafında kümelenen gelişmeler, Osmanlı edebiyatları bağlamında bir değerlendirmeye tabi tutulur. Son olarak, bu çalışmanın bir diğer iddiası, Krikor Zohrab ve Halit Ziya Uşaklıgil'i dünya edebiyatı sisteminin özneleri olarak okuyarak Osmanlı edebiyatlarından dünya edebiyatına doğru bir yol haritası çıkarmak, böylelikle imparatorluğun söz konusu dönemde deneyimlediği siyasal krizin ötesinde bir imkân üreten kültürel ve edebi etkileşimi, yazarların globalleşme ve modernlik deneyimi ile birlikte değerlendirmektir.

Literary modernization in the Ottoman Empire began to develop in the mid-nineteenth century. Moreover, the interaction between the literature within the multicultural and multilingual structure of the empire, and more specifically the increase of cross-cultural encounters in the same period. The main aim of this thesis is to evaluate the literary production of Halit Ziya Uşaklıgil and Krikor Zohrab comparatively in the context of the Ottoman literary modernization process and to look at the imperial field from a pluralist perspective. Thus, this study will confirm a dialogue with significant realist writers of Turkish and Armenian literature, and also rethink the foundations of modern literature through Halit Ziya Uşaklıgil and Krikor Zohrab. Both of the mentioned authors have contributed considerably to the autonomy of Ottoman literature with their writings produced in the field. Finally, another key argument will be to these writers in the global platform by reading Turkish and Armenian literature in the context of the world literature system. Indeed, the Ottoman Empire experienced a significant political crisis at the turn of the century. At the same time, however, changes in the cultural and social spheres did transform the empire's perception of the world. Ultimately, a modernization process across the imperial frontier is manifested across every field. On the other hand, this process improves the relations between groups and allows plurality, including within the literary field. Thus, in the cultural and literary fields of the empire, unlike the crisis, a possibility of reconciliation is achieved by Ottoman intellectuals.
Keywords: comparative literature; cultural dialogue; Culture; Culture conflict in literature; Dünya Edebiyatı Sistemi Ottoman literature; Halit Ziya Uşaklıgil; History; History and criticism; Karşılaştırmalı Edebiyat; Krikor Zohrab; Kültür; Kültür çatışması, Edebiyatta; Kültürel Diyalog; modernization; Modernleşme; Osmanlı Edebiyatı; Osmanlı İmparatorluğu; Ottoman Empire, 1288-1918; Tarih ve eleştiri; Turkey; Turkish literature; Türk edebiyatı; world literature system